The Effectiveness of Magnetite Modified Gallic Acid Synthesized by Sonochemical Method As AuCl4- Adsorbent-Reductor - Rahmayanti, Maya; Santosa, Sri Juari; Sutarno, Sutarno; Paweni, Astuti (Indonesian Journal of Chemical Research, 2021)
In recent years gallic acid has been developed as an AuCl4- adsorbent-reducing agent. In this research, gallic acid was modified with magnetite by sonochemical method (GA-Fe3O4), and its effectiveness as an AuCl4- adsorbent was studied. GA-Fe3O4 was synthesized through one-stage (GA-Fe3O4-SK1) and two-stage (GA-Fe3O4-SK2) methods. The effectiveness of GA-Fe3O4 was studied through optimization studies on pH, time, kinetics, and isotherm adsorption of AuCl4-. The adsorption method used was the batch method in the pH range 2-7. While the kinetics model used was the Lagergren and Ho kinetics model. The adsorption isotherm model used was the Freundlich and Langmuir isotherm model. The results showed that the optimum pH conditions for adsorption of AuCl4- on GA-Fe3O4 occurred at pH 3. Adsorption of AuCl4- on GA-Fe3O4-SK1 and GA-Fe3O4-SK2 both followed the Ho kinetic model, while the adsorption isotherm followed the Freundlich isotherm model with values KF were 0.041 and 0.034 mol/g respectively.